Pengaruh Rekrutmen dan Kompensasi terhadap Kinerja Karyawan PT. UBK - Annisa Apriliani; Amilia Tresnawati (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to determine the various elements, such as efficient hiring practices and equitable compensation, that affect PT. UBK employees’ performance. The researchers employed a quantitative approach to collect data, distributing a likert scale questionnaire to 100 PT. UBK personnel. The slovin formula was used to choose the sample. According to the study’s findings, the regression coefficients for the constant variable (a) is 3. 405, variable X1 (reception) is 0. 449, and variable X2 (compensation) is 0. 382. It is evident from these results that variable X2 (compensation) increased the least. Employee performance is significantly impacted by the simultaneous hiring and payment processes. The f count was 42. 871 when we employed a joint test known as the f test, which is greater than the f table value of 3. 09. This indicates that we accept the alternative hypothesis (Ha) and reject the null hypothesis (H0). The t count for recruitment (X1) is 7. 334 based on the individual test utilizing the t test, which is greater than the t table value of 1. 984. Since the Ttable value of 1. 984 is lower than the computed t value for compensation (X2), H0 is likewise rejected and Ha is approved. The coefficient of determination test’s R Square comes out at 0. 469, or 46.9%.